STATUS AND ORIENTATION FOR THE DEVELOPMENT OF HARD CLAM CULTIVATION IN NAM DINH PROVINCE - Thanh, Nguyen Xuan; Thuoc, Pham; Khoi, Tran Cong (Vietnam Journal of Marine Science and Technology, 2014)
Nam Dinh province is very potential to develop hard clam cultivation. Recently, it is reported that both the total area for growing hard clams and the total harvest increased quickly from 700ha and 13,000tons in 2005 to 1,700ha and 20,000tons in 2011 respectively. However, there is an occurrence of several problems leading to an unsustainable culturing operation, including unprompted hard clam aquaculture, lost of comprehensive plans, inappropriate invests for studying scientific techniques, and dependence of natural seed stocks. Additionally, due to ineffective governance and complication in the culturing operation process, hard clam products are mainly soled in gross types with unstable prices. In the short term, in order to goal sustainable development of hard clam culture and to harvest 31,550 tons in 2020 with an annual increase of 6%, all problems listed above should be treated completely.